2008
DOI: 10.1038/sj.bjc.6604383
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells in oncology: pitfalls and promises

Abstract: Adequate blood supply is a prerequisite in the pathogenesis of solid malignancies. As a result, depriving a tumour from its oxygen and nutrients, either by preventing the formation of new vessels, or by disrupting vessels already present in the tumour, appears to be an effective treatment modality in oncology. Given the mechanism by which these agents exert their anti-tumour activity together with the crucial role of tumour vasculature in the pathogenesis of tumours, there is a great need for markers properly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 30 publications
2
70
0
3
Order By: Relevance
“…A subsequent study by the same group has suggested that an elevated CEC level before treatment commencement predicted clinical benefit from the combination of metronomic chemotherapy and bevacizumab in metastatic breast cancer (Dellapasqua et al, 2008). However, although these results are intriguing, it should be noted that the appropriate enumeration of CECs is technically challenging (Strijbos et al, 2008). Interestingly, comparative data from four phase II clinical trials of anti-VEGF agents presented at ASCO this year in which an identical technology was used to measure CECs indicated that changes in CEC/CEP levels did not demonstrate a consistent pattern but were dependent on the antiangiogenic agent used and the treatment context (Duda et al, 2008).…”
Section: Future Prospects and Challenges In Antiangiogenic Treatmentmentioning
confidence: 73%
“…A subsequent study by the same group has suggested that an elevated CEC level before treatment commencement predicted clinical benefit from the combination of metronomic chemotherapy and bevacizumab in metastatic breast cancer (Dellapasqua et al, 2008). However, although these results are intriguing, it should be noted that the appropriate enumeration of CECs is technically challenging (Strijbos et al, 2008). Interestingly, comparative data from four phase II clinical trials of anti-VEGF agents presented at ASCO this year in which an identical technology was used to measure CECs indicated that changes in CEC/CEP levels did not demonstrate a consistent pattern but were dependent on the antiangiogenic agent used and the treatment context (Duda et al, 2008).…”
Section: Future Prospects and Challenges In Antiangiogenic Treatmentmentioning
confidence: 73%
“…Unbound cells and the remaining plasma as provided in the CellSearch Epithelial Cell kit. As CD146 enriches for circulating endothelial cells (CECs) [15], and CECs can express cytokeratin 18 [16], a marker to exclude the cytokeratin 18-expressing subset of CECs was needed. As CD34 is a pan-endothelial marker [17] …”
Section: Enumeration Of Epithelial Cells Spiked In Whole Bloodmentioning
confidence: 99%
“…While leukocytes can be excluded with CD45, which is already incorporated in the standard CellSearch Circulating Epithelial Cell kit, we assessed whether CECs could be excluded with CD34, a pan-endothelial marker [15,17]. CD34 proved to be a suitable marker to distinguish CTCs from CECs, as none of the normal-like cell lines expressed CD34 as determined by flow cytometry (Table 1).…”
Section: Cd34 To Distinguish Ctcs From Cecsmentioning
confidence: 99%
“…Alterations in CEC numbers is likely to reflect vascular damage (Strijbos et al, 2008), but no consistent changes in CEC numbers could be seen, either during therapy or between the two sunitinib doses explored. In contrast to Phase I sunitinib ifosfamide P Hamberg et al monotherapy with sunitinib (Deprimo et al, 2007), no consistent pattern in the changes in plasma concentrations of VEGF and sVEGFR2 was observed.…”
Section: Discussionmentioning
confidence: 99%